2021
DOI: 10.3390/ijerph18020689
|View full text |Cite
|
Sign up to set email alerts
|

Information or Habit: What Health Policy Makers Should Know about the Drivers of Self-Medication among Romanians

Abstract: We use the Knowledge, Perceptions and Practices framework to analyze determinants of three types of self-medication practices in Romania: (1) self-medication in the case of cold/flu/viral infections; (2) taking non-prescribed medicine in general; and (3) self-medication based on recommendations by others. We analyzed 706 responses to an online survey and used a factor-based Partial Least Squares algorithm (PLSF) to estimate the relationships between each type of self-medication and possible predictors. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
8
0
2
Order By: Relevance
“…Not last, the focus on trust could also beneficial for non-chronic patients, in reinforcing rational medicine use and in offsetting the prevalent self-medication practices observed in Romania [ 87 , 88 ], especially with non-prescription (over-the-counter) medicines and traditional remedies [ 89 ]. The results obtained for chronic patients are far-reaching in light of the existing evidence showing that a more efficient path to patient adherence in medical care settings is achieved through trust rather than satisfaction [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not last, the focus on trust could also beneficial for non-chronic patients, in reinforcing rational medicine use and in offsetting the prevalent self-medication practices observed in Romania [ 87 , 88 ], especially with non-prescription (over-the-counter) medicines and traditional remedies [ 89 ]. The results obtained for chronic patients are far-reaching in light of the existing evidence showing that a more efficient path to patient adherence in medical care settings is achieved through trust rather than satisfaction [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan hasil tersebut, dapat disimpulkan bahwa isolasi mandiri mempengaruhi hampir semua aspek kebutuhan manusia, seperti biologis, psikologis, sosial, spiritual dan budaya. Penggunaan obat-obatan pencegahan yang terkait dengan COVID-19 Nasir et al, (2020) Pengobatan sendiri terjadi karena pemberitaan di media, internet, dan kepanikan tentang kelangkaan obat Makowska et al, (2020) Perilaku terkait pengobatan sendiri telah meningkat selama penguncian karena COVID-19 Druică et al, (2021) Pengobatan sendiri dipengaruhi oleh kebiasaan dan gejala yang sama dengan orang lain Sadio et al, (2021) Prevalensi pengobatan sendiri meningkat sebagai upaya pencegahan COVID-19 Zhu et al, (2021) Peresepan antibiotik spektrum luas meningkat selama pandemi COVID- 19 Heydargoy, (2020) Pengobatan sendiri dan penggunaan antibiotik dapat menyebabkan krisis resistensi terhadap antibiotik Quispe-cañari et al, (2020) Mayoritas responden melakukan pengobatan sendiri untuk mengobati gejala pernapasan seperti flu Kebutuhan psikologis Herat, (2020) Isolasi mandiri secara paksa menyebabkan masalah kesehatan mental Terry et al, (2020) Gangguan mood akibat pembatasan COVID-19 berisiko psikopatologi Fancourt et al, (2021) Tingkat depresi dan kecemasan tertinggi terjadi pada tahap awal pembatasan wilayah COVID-19. Xiao et al, (2020) Kecemasan dikaitkan dengan stres dan penurunan kualitas tidur Ubara et al, (2020) Efek isolasi mandiri akibat COVID-19 relatif berkurang setelah satu tahun Reiss et al, (2020) Individu menghadapi ancaman selama isolasi mandiri Attal et al, (2020) Stres mental dapat disebabkan oleh kurangnya kepercayaan diri atau sumber perawatan diri Chan et al, (2020) Selama pandemi COVID-19, ada ketergantungan yang besar pada penyedia layanan kesehatan informal di rumah Glintborg et al, (2021) Kecemasan meningkat pada pasien yang memiliki kondisi komorbiditas atau komorbiditas Makowska et al, (2020) Kondisi keuangan masa depan membuat masyarakat khawatir dengan kesehatannya Ferreira et al, (2021) Individu yang dikarantina di rumah melaporkan kecemasan sebagai konsekuensi sosial dan ekonomi dari pandemi COVID-19 Song et al, (2021) Informasi yang berlebihan menyebabkan kesedihan, kecemasan, dan disonansi kognitif Hanif et al, (2021) Sering terpapar media sosial memiliki hubungan yang signifikan dengan kecemasan akibat informasi Sallie et al, (2020) Orang yang stres selama periode isolasi diri lebih cenderung menyalahgunakan alkohol.…”
Section: Hasil Dan Pembahasanunclassified
“…There are many individual-level factors associated with self-medication using antibiotics in Europe. Some of these determinants are related to individuals' feelings of illness, with multiple studies noting that self-medication is triggered in particular by upper respiratory tract symptoms, fevers, common colds, sore throats, or conditions with similar symptoms to a previous illness for which antibiotics were prescribed (Scicluna et al 2009, Skliros et al 2010, Shabani, Redican 2018, Druicȃ et al 2021. More recently, research in Australia has also found that COVID-19 pandemic-induced psychological distress has been a trigger for preventive self-medication with antibiotics (Zhang et al 2021).…”
Section: Drivers Of Antibiotic Use and Self-medicationmentioning
confidence: 99%
“…Demographic and knowledge-related correlations with self-medication behaviours have been inconsistent across studies in Europe. McNulty et al (2006McNulty et al ( , 2007b, for example, found in the UK that higher levels of knowledge about antibiotics were associated with both higher course completion and also the storing of antibiotics for self-medication, whilst other studies in Europe have found that lack of knowledge is associated with greater propensity for self-medication (Horvat et al 2017, Machowska, Lundborg 2019 or had no significant bearing (Druicȃ et al 2021). Again, there are discrepancies in European studies regarding the association of self-medication with demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%